Pengelolaan Stres Akademik Dan Kesehatan Mental Peserta Didik: Strategi Manajemen Kelas yang Berpusat pada Siswa - Siti Fatimah; chairunisa; Torikhotul Maqrifah; Linardo Pratama (Asosiasi Asesmen Pendidikan, 2026)
Academic stress and mental health issues among students are crucial issues that affect academic performance and overall psychological well-being. This study aims to analyze the role of student-centered classroom management strategies in managing academic stress and improving students' mental health. Using a literature review method, this study analyzes various theoretical and empirical sources related to stress factors, psychological impacts, and interventions in classroom management. The study shows that the use of an authoritarian approach and external pressure actually worsens students' mental health. On the other hand, a student-centered classroom management approach that focuses on autonomy, emotional support, and cooperative interaction has been proven effective in reducing stress levels. The use of practical techniques such as mindfulness and the development of adaptive coping strategies in the classroom are recommended as preventive and curative measures for educators to build a healthy and supportive learning environment.